Characterization of NtSTOP1-regulating genes in tobacco under aluminum stress. Issue 3 (4th May 2019) - Ito, Hiroki; Kobayashi, Yuriko; Yamamoto, Yoshiharu Y.; Koyama, Hiroyuki
ABSTRACT: Zinc finger transcription factors, STOP1-like proteins, are conserved among land plant species and control the expression of aluminum tolerance genes in various plant species. We performed transcriptome analyses in tobacco ( Nicotiana tabacum ) to identify NtSTOP1-regulating Al tolerance genes, the expression of which was regulated by their STOP1-like proteins, and then compared them with those in Arabidopsis ( Arabidopsis thaliana ) and rice ( Oryza sativa ). A commercially available oligo microarray identified 96 genes in a NtSTOP1- RNAi tobacco line that showed lower expression levels than in the wild type under Al stress. It was shown that most NtSTOP1 controlled genes were common to both Arabidopsis and rice, although some were missing in Arabidopsis, which is more sensitive to Al than tobacco and rice. For example, NtSTOP1 regulated the expression of orthologs of rice STAR1, the expression of which was regulated by the STOP1-like protein ART1 in rice, but not in Arabidopsis. The NtSTOP1- RNAi line showed lower expression levels of genes involved in N-metabolism, including additional genes which were not regulated by STOP1 in Arabidopsis. In addition, NtSTOP1 controlled the expression of several genes for enzymes of fermentation pathways, although it was not identified in Arabidopsis. We also revealed the NtSTOP1 binding site containing the GGNVS motif of the NtMATE promoter. The motif that causes STOP1/NtSTOP1 to bind to AtALMT1 / NtMATE, respectively, was similar, but AtALMT1 and NtMATE are fundamentally different genes. This difference in the STOP1-regulating system between tobacco and Arabidopsis is linked to differences in mutations in cis-elements in several target genes.